2009
DOI: 10.1016/j.pnpbp.2009.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Distinct effects of acute and chronic sleep loss on DNA damage in rats

Abstract: The aim of this investigation was to evaluate genetic damage induced in male rats by experimental sleep loss for short-term (24 and 96 h) and long-term (21 days) intervals, as well as their respective recovery periods in peripheral blood, brain, liver and heart tissue by the single cell gel (comet) assay. Rats were paradoxically deprived of sleep (PSD) by the platform technique for 24 or 96 h, or chronically sleep-restricted (SR) for 21 days. We also sought to verify the time course of their recovery after 24 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 54 publications
2
38
0
1
Order By: Relevance
“…In addition, central fragments from the kidney, heart, liver, and brain (prefrontal cortex) were also collected and minced in 0.9% NaCl in preparation for the comet assay. The sub-region of the prefrontal cortex was chosen based on results from our previous studies (16,17,19). The samples were maintained at -80°C until the assays were performed.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, central fragments from the kidney, heart, liver, and brain (prefrontal cortex) were also collected and minced in 0.9% NaCl in preparation for the comet assay. The sub-region of the prefrontal cortex was chosen based on results from our previous studies (16,17,19). The samples were maintained at -80°C until the assays were performed.…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, increasing attention has been given to the genetic changes that are caused by sleep loss in different contexts of SD (16,19). Recently, we demonstrated that SD induces genetic damage in the blood and brains cells of male rats (16), indicating that lack of sleep leads to severe molecular damage (19).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our group has demonstrated that PSD promoted genetic damage to the blood, brain and liver in rodents [18,19,20]. However, the consequences of sleep loss, acute or chronic, in the elderly and on skin integrity remain unknown in animal models.…”
Section: Introductionmentioning
confidence: 99%
“…Stress, lack of sleep, irregular nutrition, and environmental factors are also known or suspected to cause DNA damage. [25][26][27] It is clearly difficult to design a study that can isolate for the pure effects of WAG. Importantly, however, chronic exposure to WAG has yet to be proven harmless.…”
Section: Discussionmentioning
confidence: 99%